The Use of Fix-Up Strategy to Improve Reading Comprehension of the Eleventh Grade Students of Senior High School - Awaluddin, Muktamirah; Abdul Kamaruddin; Wahyudin; Anjar Kusuma Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The objective of this research is to find out whether the use of Fix-up Strategy can improve reading comprehension of the eleventh-grade students’ MA Alkhairaat Biromaru. This research used a pre-experimental research. The sample of this research was class XI IPS MA Alkhairaat Biromaru which consisted of 16 students. The sample was obtained by using purposive sampling technique. The data were collected using tests, pretest and posttest, and analyzed statistically. The result of this research showed that there is significant differences of students’ achievement in pretest and posttest. It shows that the mean score of the pretest is 53.44 and the mean score of posttest is 66.72. The result showed that the value of t-counted (10.60) is higher than the value of t-table (1.753) by applying a significance level of 0.05. It means that the hypothesis is accepted. Thus, the use of fix-up Strategy can improve reading comprehension of the eleventh-grade students MA Alkhairaat Biromaru.